LTX-315 triggers anticancer immunity by inducing MyD88-dependent maturation of dendritic cells - Li, Xiao-Qing; Yamazaki, Takahiro; He, Tianzhen; Alam, Md Masud; Liu, Jia; Trivett, Anna L.; Sveinbjørnsson, Baldur; Rekdal, Øystein; Galluzzi, Lorenzo; Oppenheim, Joost J.; Yang, De (Frontiers in Immunology, 2024)
LTX-315 is a synthetic cationic oncolytic peptide with potent anticancer activity but limited toxicity for non-malignant cells. LTX-315 induces both immunogenic tumor cell death and generation of tumor-specific immune responses in multiple experimental tumor models. Given the central role of dendritic cell (DC) maturation in the induction of antigen-specific immunity, we investigated the effect of LTX-315 treatment on the maturation of tumor-infiltrating DCs (TiDCs) and the generation of anti-melanoma immunity. We found that LTX-315 treatment induces the maturation of DCs, both indirectly through the release of cancer cell-derived damage-associated molecular patterns (DAMPs)/alarmins and nucleic acids (DNA and RNA) capable of triggering distinct Toll-like receptor (TLR) signaling, and, directly by activating TLR7.The latter results in the ignition of multiple intracellular signaling pathways that promotes DC maturation, including NF-kB, mitogen activated protein kinases (MAPKs), and inflammasome signaling, as well as increased type 1 interferon production. Critically, the effects of LTX-315 on DCs the consequent promotion of anti-melanoma immunity depend on the cytosolic signal transducer myeloid differentiation response gene 88 (MyD88). These results cast light on the mechanisms by which LTX-315 induces DC maturation and hence elicits anticancer immunity, with important implications for the use of LTX-315 as an anticancer immunotherapeutic.